Impact of location and deadband on energy performance of nano aerogel glazing for office building in Saudi Arabia. Issue 6 (17th August 2020) - Abdul Mujeebu, Muhammad; Ashraf, Noman
ABSTRACT: The present study has focused on the impact of location and deadband (range of thermostat setpoints for cooling and heating) on the energy performance and economics of nano granular silica aerogel (nanogel) glazing in a multi-storey office building, by considering 26 climatic locations of Saudi Arabia. The selected cities were classified according to the cooling degree days (CDD) and outdoor dry bulb temperature (DBT), as warm, moderately hot, hot, and very hot, and the results were generalized with respect to these climatic zones. The building model was built in Autodesk Revit (2015), and the energy simulation was performed by Ecotect (2011) in two cases: (i) insulated wall and roof, and DG window and (ii) insulated wall and roof, and nanogel glazing. The results show that the location and deadband have crucial impact on the energy performance and economic viability of nanogel glazing. The energy-saving potential and payback period of replacing DG window by nanogel glazing are attractive for cities with higher DBTs and CDD, compared to those with lower DBT and CDD. For all the climatic zones studied, the benefit of replacing DG window by nanogel glazing could be achieved for a specific deadband of 20–24°C.